Analysis of the World and Russian E-Commerce Market: Development Trends and Challenges - Vladimirovna Pavlova, Elena; Aleksandrovna Silayeva, Anna; Nikolaevna Borisova, Oksana; Gennadiyevna Doronkina, Irina; Pavlovna Sokolova, Antonina (International Journal of Engineering and Technology, 2018)
The informational support of the society and its constituent parts from individuals to organizations and states leads to speeding up the decision-making process, and, consequently, to speeding up the process of movement of goods and services which are now being carried out via the Internet. There is no doubt that electronic commerce (e-commerce) will become one of the dominant types of trade and one of the promising components of the "new economy" in the foreseeable future.The popularity of e-commerce is growing rapidly under the influence of various factors and now we cannot imagine the modern world without online stores and all kinds of mobile applications that help to make purchases at all levels.It goes without saying that e-commerce (online trade) will develop most rapidly in the most technologically advanced countries, such as the states of Europe, North America, Japan and China, having their own characteristics depending on national, demographic and other factors. The Russian government that Âtried to modernize the country has been shown a high rate of development of information technology and e-commerce over the past 15 years, but just in the European part of the country to a greater extent; it is related to the demographic state of the country. But the expansion of industry in the East (construction of new roads, ports, factories, agro-industrial and military-industrial complexes) creates a favorable environment for business in general and for e-commerce, in particular. The investment attractiveness of the Far East region also plays an important role. The changing way of life of the population and the technological breakthrough create new information and technological nation-wide economic environment that develops in close connection with the world economic development trends experiencing their influence, and in turn influencing them.Â Â